Jawabanmu

Jawaban paling cerdas!
2014-05-28T14:45:07+07:00
L i m  4xSin x  = l i m  4xSinx
x⇒0  1-Cos4x    x⇒0  2Sin²x
                       = l i m   4x      
                         x⇒0  2Sin2x
                       = 4/2(2)⇒
                       = 4/4
                       = 1

L i m  1 - 2Sin²x  = l i m    Cos²x - Sin²x
x⇒π/4 Cosx-Sinx  x⇒π/4 Cosx - Sinx
                             = l i m (Cosx - Sin x)(Cosx+Sinx)
                               x⇒π/4  (Cosx - Sinx)
                             = L i m (Cosx + Sinx)
                               x⇒π/4
                             = Cosπ/4 + Sinπ/4
                             = 1/2 √2 + 1/2√2
                             = √2
1 5 1